CO-CREATION SEBAGAI INOVASI PELAYANAN PUBLIK DI DISDUKCAPIL KOTA BANDUNG - Ezra Khagi Himura; Tomi Setiawan (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2022)
This research describes co-creation as innovation in public services. Co-creation places the community not only as beneficiaries, but also as collaborators. This research aims to describe the process of co-creation in Disdukcapil of Bandung City through the creation of an innovation environment, and the extent of community involvement in co-creation process based on the engagements of explorer, ideator, designer, and diffuser. This research used a qualitative approach with data collection techniques through study literature, observation, and interview. Data analysis was carried out through data condensation, data display, and data verification. The implications of this research can be used as considerations for Disdukcapil of Bandung City in improving co-creation as service innovation. This research found the application of co-creation as service innovation in Disdukcapil of Bandung City through the creation of an innovative environment was quite good and the involvement of community in co-creation of Disdukcapil of Bandung City was still focused on citizen engagement as explorer and ideator, while involvement as designer and diffuser was relatively still limited. The recommendation from this research is that Disdukcapil collaborates with the community through strengthening citizen engagement as designers and diffusers so that the community can be fully involved in implementation of services provided.